COMPARISON OF CUT AND FILL VOLUME USING PHOTOGRAMMETRIC MEASUREMENT AND TOTAL STATION MEASUREMENT (Georest, 2022)
Survey activities at the time of mine exploitation aim to map the progress of the mine and to determine the total volume of overburden and coal that has been mined. Currently, the work of mapping surveys has begun to be replaced by observations of recorded data without touching the object or aerial shooting using aircraft or called photogrammetry . The purpose of this study was to determine the difference and difference in volume of autogrammetric processing with volume from survey processing using total stations. From the volume results obtained from the photogrammetric measurements, it will be reduced by the total station survey volume which is considered correct, which is 441,404,769 BCM. The difference between the Cut and Fill Volume of PIT A using Drones and the Volume of Surveys using Total Station is 166,655,453 BCM or around 37.76%. From the difference in the volume of Cut and Fill photogrammetry using each number of GCP points with the volume of Cut and Fill survey total station it can be concluded that the more the number of points GCP then the volume will be closer to the survey volume using Total Station.